Khotedjing phonkatob jak kan ped seri sinka kared te me tor kasedtakon Thai lae kho saner krueakai kasedxtakon lae pak prachacohn (Foundation of Reclaiming Rural Agriculture and Food Sovereignty Action (RRAFA))
The fact : reflections on the agriculture Free Trade Agreement and the Thai peasants and the proposal from the peasant networks and social movements.